Finite difference solution of unsteady flow past an oscillating semi-infinite vertical plate with variable surface temperature and uniform mass flux - Muthucumaraswamy, Rajamanickam; Saravanan, Balasubramani (Zielona Góra: Uniwersytet Zielonogórski)
A finite difference solution of an unsteady flow past an oscillating semi-infinite vertical place with variable temperature and uniform mass flux is presented here. The fluid considered here is a gray, absorbing-emitting radiation but a non-scattering medium. The dimensionless governing equations are solved by an efficient, more accurate, and unconditionally stable and fast converging implicit scheme. The steady state velocity, temperature and concentration profiles are shown graphically.
Keywords: radiation; vertical plate; finite-difference; variable temperature; uniform mass flux